Pengaruh Kecerdasan Emosional, Disiplin Kerja Dan Kepuasan Kerja pada Komitmen Organisasi pekerja DPKPP Kota Probolinggo - Zakaria, Fiqih Zakaria; Elmas, Muhammad Syarif Hidayatullah; Hermawan, Dedi Joko (Universitas Panca Marga, 2024)
This study aims to determine whether the influence of Emotional intelligence, Work discipline and Job satisfaction has a simultaneous and partial effect on employee organizational commitment DPKPP probolinggo city. And also among these three variables, which variable has the most dominant effect on the dependent variable (organizational commitment). The type of research used is descriptive quantitative, with the variables emotional intelligence,work discipline and job satisfaction, the number of samples in this study were 59 respondents. The test results show that it partially affects the level of organizational commitment at DPKPP probolinggo city. The partial test results show that emotional intelligence (X1), work discipline (X2), and job satisfaction (X3) of the three variables have significant values. Thus the results of the t (partial) test show that there is a positive and significant influence of variable emotional intelligence, work discipline and job satisfaction on the level of organizational commitment at DPKPP, City of Probolinggo. Keywords : Emotional intelligence, Work discipline, Job satisfaction, Organizational commitment.